KOMPETENSI LULUSAN FAKULTAS TARBIYAH DALAM MENGHADAPI PASAR GLOBAL - Maidar Darwis (Jurnal Ilmiah Didaktika, 2011)
Nowadays, after free trade area has openned, the alumni of higher education (including Tarbiyah Faculty) have to win the competition from other higher institutions alumni by having high competence in their field of study. They must have good knowledge on their field and be skillful. The additional skills that are necessary to face the global competition are having foreign language competences (English and Arabic), mastering computer/internet, having high working ethic, being able to work in team, and being able to express themselves. To develop the main competences is the duty of department, while, the additional one is the duty of faculty. If the alumni do not have any additional competences, they will be difficult to get a job. They will be jobless because of their incapability to compete with others. Abstrak